Paediatric end of life care pathway. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Gold, Libby; Wyllie, Julie; Gray, Sarah; McKean, Helen
Abstract : Background: Children's Association Scotland (CHAS) is Scotland's only children's hospice organisation and has two hospices: Rachel House in Kinross and Robin House in Balloch. In addition there is a CHAS at Home service. Aim: The aim of the project was to ensure that a consistent high standard of care was given to all children and young people at the end of life by developing a Paediatric End of Life Care Pathway (PEoLCP). Methods: A multi-disciplinary working group was established at Robin House. A review of literature was undertaken, and findings recommended a care pathway approach to support the delivery of a good quality of care during the end stages of life. Existing care pathways were also reviewed however, these were not appropriate to the paediatric setting. The group then identified the main presenting symptoms and care requirements for children and young adults at the end of life and developed a pathway specifically to address these. This incorporated elements from the Rainbow Children's Hospice Guidelines (2011). Findings: The PEoLCP was piloted and reviewed in Robin House. The feedback concluded that using a PEoLCP helped the care staff provide proactive rather than reactive care. As a valuable 'one-stop' document it improves communication between disciplines, ensuring a holistic approach to care for the child and their family. It is now in use throughout CHAS. It is for the multidisciplinary team. Conclusions and Recommendations: This pathway could be used in any setting for the care of children and young people at end of life. CHAS has recommended that the Scottish Children's and Young People's Palliative Care Executive (SCYPPEx) consider its use throughout Scotland. References: Jassal, S.S. (2011) Basic Symptom Control in Paediatric Palliative Care. The Rainbow Children's Hospice Guidelines 8th Edition (online) ACT: www.act.org.uk accessed 19 July 2011.